A study on the intervention effect of a case management model that breaks through spatiotemporal characteristics in home-based phase II exercise rehabilitation post PCI - Jin, Haiqin; Wu, Lingsha; Huang, Ping; Zheng, Yeping; Sun, Yan; Lu, Qin; Meng, Xiaoqin; Yu, Zhifang (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveThis study aims to explore the effect of a case management model that breaks through the temporal and spatial characteristics on the at-home phase II exercise rehabilitation of postoperative patients treated with percutaneous coronary intervention (PCI).MethodsWe used the convenience sampling method to select 103 patients with coronary artery disease (53 in the observation group and 50 in the control group) who were admitted to the Department of Cardiovascular Internal Medicine at the Jiaxing No. 2 Hospital in January 2022 and January 2023 and underwent PCI treatment as study subjects. Patients in the control group were managed by the conventional continuity of care model, and those in the observation group were managed by the case management model that breaks through the temporal and spatial characteristics. Both groups of patients were intervened and followed up for 6 months, comparing the adherence to home II exercise rehabilitation and regular follow-ups, coronary heart disease risk factor indexes, unplanned readmission rate, and the incidence of adverse cardiovascular events between the two groups of patients.ResultsExercise adherence and regular follow-up adherence of patients discharged from the hospital at 1, 3, and 6 months after PCI were higher in the observation group than in the control group (P < 0.05). The comparison of risk factor indicators of patients in both groups at 6 months after discharge with those of patients before discharge showed different degrees of improvement, and the difference was statistically significant (P < 0.05). However, the difference in fasting blood glucose in the control group at 6 months after discharge compared with that before discharge was statistically significant (P < 0.05), whereas there was no statistical significance in the observation group (P > 0.05). The incidence of major adverse cardiovascular events and unplanned readmission at 6 months after discharge between the two groups was lower in the observation group than in the control group, and the difference was statistically significant (P < 0.05).ConclusionThe case management mode that breaks through the spatiotemporal characteristics can improve the exercise adherence and regular follow-up adherence of post-PCI patients’ at-home phase II exercise rehabilitation, which can effectively control the indexes of body mass index (BMI), triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) and reduce the rate of unplanned readmission and the incidence of adverse cardiovascular events.